Influence of SiO2 and ZrO2 Nanocomposite on the AC Breakdown Strength of Cross-linked Polyethylene (XLPE) - Rahman A.B.A.; Rahman M.S.A.; Ariffin A.M.; Ali N.H.N.; Ghani A.B.A.; Lau K.Y.; Mohamad M.S.; Osman M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Aliphatic compounds; Dielectric properties of solids; Filled polymers; Low-k dielectric; Nanocomposites; Polyethylenes; Silica; Silicon; Silicones; SiO2 nanoparticles; Zirconia; AC performance; Breakdown performance; Cross-linking process; Crosslinked polyethylene; Dielectric strengths; High voltage cable; Nanocomposite samples; Polymer nanocomposite; Dielectric materials